Incidence of Osteolysis and Aseptic Loosening Following Metal-on-Highly Cross-Linked Polyethylene Hip Arthroplasty: A Systematic Review of Studies with Up to 15-Year Follow-up. (21st April 2021) - Prock-Gibbs, Hannah; Pumilia, Cyrus Anthony; Meckmongkol, Teerin; Lovejoy, John; Mumith, Aadil; Coathup, Melanie
Abstract : Background: This study compared the incidence of osteolysis, aseptic loosening, and revision following use of highly cross-linked polyethylene (HXLPE) or conventional polyethylene (CPE) at medium to long-term (>5 to 15 years) follow-up in primary total hip arthroplasty (THA). Incidences were quantified and compared with regard to age and method of implant fixation. Methods: Using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) guidelines, 12 randomized controlled trials and 18 cohort studies were investigated for evidence-based outcomes following HXPLE and CPE use in 2, 539 hips over a 5 to 15-year follow-up. Results: Lower rates of osteolysis, aseptic loosening, and implant revision were reported following use of HXLPE liners. Osteolysis was reduced from 25.4% with CPE to 4.05% with HXLPE in young patients, and from 29.7% to 6.6% in the older patient cohort. Similarities in osteolysis rates were observed when cemented (24.9% for CPE and 6.5% for HXLPE) and uncemented components (32.8% for CPE and 7.1% for HXLPE) were compared. No clear advantage in the type of HXLPE used was observed. Conclusions: Over a follow-up period of up to 15 years, when compared with CPE, use of HXLPE liners reduced the incidence of osteolysis, aseptic loosening, and implant revision, regardless of the fixation method and including in younger and potentially more active patients. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.